Uniportal video-thoracoscopic mediastinal lymphadenectomy - Bedetti, Benedetta; Bertolaccini, Luca; Panagiotopoulos, Nikolaos; Scarci, Marco (Video-Assisted Thoracic Surgery; Vol 1 (December 2016): Video-Assisted Thoracic Surgery, 2016)
Systemic mediastinal lymphadenectomy has a key role in lung cancer surgery, as it permits to define the pathological staging and therefore the treatment and the prognosis of the patients. Currently the video-assisted thoracoscopic approach is the most common technique to remove these tumours, if technically feasible. Particularly the uniportal approach provides with the best anatomic instrumentation and a direct view. In this paper, we describe our technique to perform a safe an effective radical mediastinal lymphadenectomy.